Jenis dan Model Evaluasi Pendidikan di Lingkungan Pesantren - Fahmi Hasbi Arrosyad; M. Fuad Hasan (BAMALA Institute, 2025)
Islamic boarding schools (pesantren) are the oldest Islamic educational institutions in Indonesia, facing major challenges in balancing tradition with the demands of modernity. The typological diversity of pesantren—ranging from purely Salafiyah, modern (Khalafiyah), to integrated pesantren—creates variations in curriculum management and evaluation systems. This study aims to analyze the types and models of educational evaluation in pesantren through a qualitative literature review approach. The findings reveal that Salafiyahpesantren emphasize authentic and qualitative evaluation based on mastery of classical Islamic texts (kitab kuning) and students’ moral development, while modern pesantren adopt formal evaluations in accordance with government standards. Integrated pesantren, meanwhile, apply a dual evaluation system that balances formal academic achievement with the depth of religious knowledge. These findings highlight that integrating traditional and formal evaluation models is crucial to ensuring educational accountability while preserving the authenticity of pesantren.